The Equivocal Meanings of “Defunct Action” (Ahosi-Kamma) - Mahanarongchai, Sumalee; Natthan (Journal of Buddhist Studies Chulalongkorn University, 2025)
This article studies the meanings of Defunct Action (Ahosi-Kamma) in equivocal senses; a social belief and a Theravada teaching. As a belief, a defunct action means forgiveness to negative interpersonal relationships and brings hostility to the end. As a Buddhist teaching, a defunct action may mean either such intentional action already bore its fruit or lost its chance to bear fruit. In the case of intentional actions losing their chance to bear fruit, when Abhidhammic doctrines regarding the seventeen momentary minds in a flow of processing consciousness (vithi-citta) and the seven kammic-conditioning momentary minds (javana-vithi-citta) are considered, it is found that a defunct action is possible when we explain the fruit of such intentional action in association with the time of fruit-bearing. An action with intensively intentional force bearing its corresponding fruit immediately can be defunctive if a more powerful condition hinders its causal process. Also, an action with intensively intentional force waiting to bear its corresponding fruit in the nearest future can be defunctive if a more powerful condition hinders its causal process. The most powerful condition that can make intentional actions defunctive is the attainment of Nibbana.